The domestication of human birth - Stefanović, Sofija (Documenta Praehistorica, 2006)
Observations of the burial places of newborns at the prehistoric site at Lepenski Vir (Serbia) revealed the possibility that deliveries took place inside houses that were heated. Warm houses provided a thermally stable environment which, in turn, could solve the problem of thermo-regulation, that is critical for the survival of babies. In this study it is shown that the creation of these good conditions for giving birth could have been an important step in human evolution that could have led to a demographic expansion.
Keywords: Serbia; Srbija; prazgodovina; neolitik; bivališča; ogrevanje; porod; childbirth; rojstvo; novorojenčki; termoregulacija